Motivation, Self-Efficacy, and Technology on Employees’ Performance Perceptions: The Mediating Role of Knowledge Sharing at PT Brantas Abipraya (Persero) - Dimaz Yudha Pradipta Putra; Edo Chandra; Sukma Nurwibawa; Ahmad Syamil (LP2M IAIN Palopo, 2026)
This study is grounded in the gap that improvements in employees’ perceived performance in construction companies have not yet been comprehensively explained through the integrated roles of motivation, self-efficacy, knowledge management system (KMS) use, and knowledge-sharing behavior. Accordingly, this study aims to analyze the effects of intrinsic motivation, extrinsic motivation, self-efficacy, and KMS use on perceived performance, with knowledge-sharing behavior serving as a mediating variable. The study is based on Social Cognitive Theory and Self-Determination Theory, which emphasize the roles of psychological, motivational, and work-environment factors in shaping individual behavior and performance. A quantitative approach with a causal research design was employed. The population consisted of 812 employees from Operations Divisions I, II, and III of PT Brantas Abipraya (Persero), with a sample of 260 respondents selected through purposive sampling. The data were analyzed using SEM-PLS. The results indicate that intrinsic motivation, extrinsic motivation, self-efficacy, and KMS use have positive and significant effects on both knowledge-sharing behavior and perceived performance. Knowledge-sharing behavior also has a positive and significant effect on perceived performance and partially mediates all of these relationships. The dominant findings show that KMS use strongly promotes knowledge sharing, while knowledge sharing exerts the strongest effect on performance. Theoretically, these findings reinforce the relevance of both theories in the context of construction companies. Future studies are recommended to employ objective performance data, broaden the research setting, and incorporate additional variables to develop a more comprehensive model.